DIGNIFYING THE INSTITUTION OF FATWA ACCORDING TO THE PERSPECTIVE OF QAWAID FIQHIYYAH: MEMARTABATKAN INSTITUSI FATWA MENURUT PERSPEKTIF QAWAID FIQHIYYAH - Izzuddin Mohd noor, Mohd (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2022)
Fatwa is very important to the Muslim especially in facing the modern life nowadays. This is because there are many new things that require the latest fatwas to facilitate the affairs of the lives of Muslims. Therefore, the fatwa institution needs to be elevated as respected and revered organization. This study aims to see the ways that can be used to elevate the institution of fatwa from the point of view of Qawaid Fiqhiyyah. The form of this study is qualitative which gathers information from the books of turath, contemporary books, scholarly studies, as well as current fatwas related to fatwas, fatwa institutions and Qawaid Fiqhiyyah. All this information will be examined to get the best worldview related to the steps that can be taken to elevate the institution of fatwa from the perspective of Qawaid Fiqhiyyah. The results show that Qawaid Fiqhiyyah can be a guiding instrument to elevate the institution of fatwa. In conclusion, the application of Qawaid Fiqhiyyah needs to be expanded in the form of action and implementation in all fatwa institutions.